Video Edukasi terhadap Peningkatan Pengetahuan dan Minat Ibu Hamil dalam Konsumsi Tablet Tambah Darah - Mardianti Mardianti; Yuli Farida; Ratih Virta Gayatri; Dyah Noviawati Setya Arum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the effectiveness of educational videos in increasing the knowledge of pregnant women with anemia and their interest in the routine consumption of blood-supplementing tablets. A quantitative method with a quasi-experimental design was employed. Statistical analysis revealed a significant difference in effectiveness regarding the increase in knowledge (p = 0.000) and interest (p = 0.000) in routinely taking blood-supplementing tablets among pregnant women who watched the educational videos. In conclusion, the use of educational videos serves as an engaging health promotion medium; it is effective in enhancing pregnant women's knowledge regarding the independent recognition or early detection of anemia and its prevention during pregnancy, while also fostering a strong interest in the routine consumption of blood-supplementing tablets practices that contribute to a healthy pregnancy and prepare for a safe childbirth. Keywords: Anemia, Pregnant Women, Educational Video